The impact of COVID-19 pandemic restrictions on general practitioner contacts among patients with common and at-risk diagnoses: a Norwegian registry-based study - Jonas Nordvik Dale; Tone Morken; Knut Eirik Eliassen; Jesper Blinkenberg; Guri Rortveit; Valborg Baste (Scandinavian Journal of Primary Health Care)
Background Disease prevention strategies during the COVID-19 pandemic could potentially disrupt the continuity of care. Aims: (1) describe changes in contacts with general practitioner (GP) before and during the pandemic, (2) compare consultation rates for common and at-risk diagnoses, and (3) examine the impact of COVID-19 restrictions on monthly consultation rates across patient subgroups.Methods Register study with data from the Norwegian Registry for Primary Health Care (NRPHC) for the period 1 April 2018 to 30 March 2021. Changes in consultation rate were the main outcome. Twenty-five diagnoses representing common and at-risk for mortality diagnoses were studied. Interrupted time series analyses were applied.Results Face-to-face consultations decreased from 2935 to 2304 per 1000 inhabitants per year from the pre-pandemic period to the first pandemic year, with an increase in e-consultations from 60 to 846 per 1000 inhabitants per year. Consultations for common diagnoses decreased by 25.6%, whereas those for high-risk diagnoses decreased by 10.7%. In the group of common diagnoses, the decrease in average monthly consultation rates was less among the eldest compared to the youngest age group. A similar decrease was found in the group with multiple morbid conditions compared to single or no morbidity.Conclusions The pandemic resulted in fewer face-to-face consultations, but there was a substantial rise in electronic consultations. Consultations for at-risk for mortality diagnoses decreased relatively less than for common diagnoses. Consultation rates for older adults and those with multiple decreased less, suggesting that sicker patients continued to visit their GP during the pandemic.